1. The problem statement, all variables and given/known data I am asked to prove that [itex](\sim x)\vee z = \sim(x\vee y)\vee\sim(y\vee\sim z)\vee\sim(x\vee\sim y)\vee\sim(\sim y\vee\sim z)[/itex]. I've tried using all combinations of DeMoran's rule, the distributive rule to get the y terms together, and the absorption rule to get rid of the y (which is required in order to simplify it down in terms of x and z. 2. Relevant equations DeMorgan's Rule: [itex]\sim(p\wedge q) = \sim p\vee\sim q[/itex] Absorption Rule: [itex]p\vee(p\wedge q) = p[/itex] 3. The attempt at a solution I can post some of the steps I've taken, but none really lead anywhere. Where is a good place to start for a question like this?